2012
DOI: 10.1038/nn.3028
|View full text |Cite
|
Sign up to set email alerts
|

The toxic Aβ oligomer and Alzheimer's disease: an emperor in need of clothes

Abstract: The 'toxic Aβ oligomer' hypothesis has attracted considerable attention among Alzheimer's disease researchers as a way of resolving the lack of correlation between deposited amyloid-β (Aβ) in amyloid plaques-in terms of both amount and location-and cognitive impairment or neurodegeneration. However, the lack of a common, agreed-upon experimental description of the toxic Aβ oligomer makes interpretation and direct comparison of data between different research groups impossible. Here we critically review the evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
1,851
2
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,789 publications
(1,904 citation statements)
references
References 102 publications
37
1,851
2
14
Order By: Relevance
“…It is widely accepted that oligomers are predominantly responsible for the neuronal toxicity of Aβ, and that metal ions play important roles in the oligomerisation 23, 24. The English and Tottori mutations occur in the Aβ N terminus, a region that has been identified as able to bind to neurometals, such as zinc and copper.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that oligomers are predominantly responsible for the neuronal toxicity of Aβ, and that metal ions play important roles in the oligomerisation 23, 24. The English and Tottori mutations occur in the Aβ N terminus, a region that has been identified as able to bind to neurometals, such as zinc and copper.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the species formed during the aggregation reactions have a toxic effect on cells 5, 6, 7, 8. Several possible mechanisms of cellular damage have been identified with relative contributions that depend on both the concentrations and the types of aggregates present 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11. The aggregation process that results in the formation of oligomers may contribute to cellular damage 12, 13, 14, 15.…”
mentioning
confidence: 99%
“…The aggregation process that results in the formation of oligomers may contribute to cellular damage 12, 13, 14, 15. Some of these mechanisms are thought to involve specific binding to receptors on the cell membrane1, 5, 9 while others appear to be the consequence of non‐specific membrane disruption 1, 3, 5, 9, 16. A body of data suggests that small soluble aggregates, often called oligomers, rather than mature fibrils, are able to cause the membrane to become permeable to Ca 2+ resulting in Ca 2+ influx and the disruption of Ca 2+ homeostasis 2, 3, 5, 9, 17, 18.…”
mentioning
confidence: 99%
“…This is particularly interesting since the oligomer form of Aβ1‐42, and not the fibril form of this specie, is regarded as the most toxic form (Benilova, Karran & De Strooper, 2012). Our own comparative study showed that stimulation with both oligomer‐EP Aβ1‐42 and fibril‐EP Aβ1‐42 decreased HBVP viability measured by LDH.…”
Section: Discussionmentioning
confidence: 99%
“…This feature results in more heterogeneous preparations and analysis of our preparations revealed the presence of oligomers in both oligomer‐EP and fibril‐EP Aβ1‐42 preparations, whereas fibrils were only found in the fibril‐EP Aβ1‐42 preparation. We are therefore unable to unambiguously show the impact of Aβ1‐42 fibrils on HBVP viability, but the increased cell death seen in response to oligomer‐EP Aβ1‐42 exposure is in line with previous studies (Benilova et al., 2012), highlighting the different impact of the two Aβ species in regard to oligomer toxicity.…”
Section: Discussionmentioning
confidence: 99%